A estrutura de capitais dos hoteleiros e a ocupação do litoral de Maceió - AL - Carvalho, Antonio Daniel Alves (2022)
This thesis adopts the theoretical-methodological perspective of economic sociology to investigate the structure of capital composition of hoteliers who take ownership of the Seafront area of Maceió, a place that has one of the most expensive square meters in the city, in addition to having a leisure structure available for their patrons. Access to the sea, or sea views, taken as symbolic capital for status, is a relatively recent social construction, since, even in the 19th century, the coast was seen as an exotic and hostile place, where few trailblazers dared to venture. In Maceió, the historical resignification of housing by the waterfront as a leisure space led to the occupation of the coast by the summer houses of wealthy families, followed by an urbanization process undertaken by the city's public agents, making the waterfront the main postcard of the city. This thesis works with two hypotheses: (i) the first one assumes that the process of transformation and occupation of Maceió’s waterfront coincides with transformations on the hotel industry in the city (ii) the second, implied by the first, assumes that the analysis of the capital structure of the collective of hoteliers could reveal the operating logic on the hospitality subfield, and therefore, the logic of occupation of the coast. We divided the history of the hotel industry into three moments: moment T1 - from 1950 to 1970 - when hotels mainly occupied the center of the city and underwent a process of professionalization; moment T2 - 1970 to 2000 – a period of development on the sector in Maceió, with the arrival of mass tourism and an the fast-passed occupation of the city's seafront by hotels, and the moment T3 - from 2000 to 2019 - the hotel industry establishes itself occupying the seafront of Maceió, dividing the spaces in correspondence with the capital structures of their hoteliers. Over the years of developing the thesis, data was gathared from hotels and their owners. A prosopography was carried out with secondary biographical data, wich allowed the construction of the hotel subfield of Maceió. Using the theoretical and methodological guidelines of Bourdieusian economic sociology, we identified the economic, social, cultural, educational/technological capital of hoteliers. From the systematic organization of capital, it was possible to identify a symbolic dispute between local hoteliers and outsiders: locals occupy privileged spaces and are involved in the constitution of public policies aimed at tourism, while outsiders occupy the space “of inside” and do not engage in these public policies. The analysis of the capitals showed that it is possible to associate the moment T1 with the domestic world, the T2 with the industrial world and the T3 with the mercantile world. Each of these worlds (cité) are the orders of justification that define morality and ethics in a given social grouping, according to Boltanski and Thévenot. Finally, it was also possible to identify that the occupation Maceió’s coast is the result of social reproduction performed by a group of families that reconvert their capital to remain dominant in Maceió’s hotel industry.